Air Fixation and AFM: A Comparative Study of Nanoparticle-Induced Topographical Changes in Lung Cells - Gamze Yeşilay (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
Gold nanoparticles (AuNPs) have emerged as promising agents in biomedical applications due to their unique physicochemical properties. This study investigates the cellular interactions of AuNPs with A549 (non-small cell lung adenocarcinoma) and BEAS-2B (normal bronchial epithelial) cell lines. AuNPs were synthesized via the citrate reduction method, resulting in 20, 50, and 70 nm particles.Cells were incubated with AuNPs for increasing durations (30 minutes, 4 hours, and 24 hours). Post-incubation, cells were washed with PBS, air-fixed, and subsequently analyzed using Atomic Force Microscopy (AFM) to obtain detailed topographical maps. AFM imaging revealed distinct interactions between AuNPs and the two cell lines. A549 cells displayed darker regions on the cell surface, indicative of topographical depressions likely resulting from nanoparticle-induced membrane collapse. In contrast, BEAS-2B cells did not exhibit such depressions, which is consistent with the literature that suggests cancer cells are mechanically softer than normal cells.The surface roughness analysis results indicated that the preservation of surface integrity post-fixation validates the air-fixation methodology for obtaining reliable mechanical data from AFM analyses.